Marketing strategy as a tool for ensuring the economic security of the enterprise - Lysytsia , N.V. (Ways to Improve Construction Efficiency, 2023)
It has been proven that the creation of a system of economic security and its effective management is necessary to counteract and fight against various threats and dangers. The place of the marketing component in the economic security of the enterprise is defined. The importance of an effective marketing strategy for ensuring economic security and successful functioning of the enterprise is considered. Marketing is defined as a management function that seeks to increase the target market, build long-term relationships, satisfy customers, ensure desired profitability and strengthen competitive advantage. Theoretical approaches to the implementation of anti-crisis management were studied, specific features of supporting the economic security of construction enterprises in the short-, medium- and long-term periods were determined. The main functional goals of economic security of the enterprise are highlighted. A brief description of individual stages of management of the enterprise's economic security system is provided. It is proposed to divide the process of managing the economic security of the enterprise into the following stages: setting and justifying goals for ensuring the financial security of the enterprise, identifying the problem, establishing restrictions to minimize the financial losses of the enterprise, developing a set of measures aimed at eliminating the identified problem, making the optimal decision regarding ensuring financial and economic security of the enterprise, coordination of the adopted decision with the management of the enterprise, ongoing monitoring of the implementation of the adopted strategy. Trends in the development of construction enterprises were studied, and their features were identified: phasing of construction works; diversity of industrial relations; duration of the production cycle; stationarity of the construction object; high manufacturability of modern construction production. It has been analyzed that any construction project can be divided into three stages: construction preparation, execution of construction works and commissioning of the finished construction object. The most important reasons for the bankruptcy of construction enterprises are given, which are as follows: ineffective marketing, ineffective policy of providing the opportunity to buy apartments in installments, increased production costs due to the use of outdated technologies.